2020
DOI: 10.1136/bmjopen-2019-031468
|View full text |Cite
|
Sign up to set email alerts
|

‘Building on shaky ground’—challenges to and solutions for primary care guideline implementation in four provinces in South Africa: a qualitative study

Abstract: ObjectivesClinical guidelines support evidence-informed quality patient care. Our study explored perspectives of South African subnational health managers regarding barriers to and enablers for implementation for all available primary care guidelines.DesignWe used qualitative research methods, including semistructured, individual interviews and an interpretative perspective. Thematic content analysis was used to develop data categories and themes.SettingWe conducted research in four of nine South African provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Professional nurses expressed concerns regarding delays in reporting broken equipment and machines, as well as the long period taken to have them fixed. This finding concurs with the study by Kredo, Cooper, Abrams, et al, conducted in four provinces in South Africa, which suggested an urgent need for the National Department of Health (NDoH) to prioritize the existing challenges in the healthcare system in accessing and using medical supplies, which impacted adherence to guidelines [27]. Steinhobel, Mossyn, and Peer outlined that the implementation of the IC program includes maintenance of the infrastructure and the availability of resources [28].…”
Section: Discussionsupporting
confidence: 87%
“…Professional nurses expressed concerns regarding delays in reporting broken equipment and machines, as well as the long period taken to have them fixed. This finding concurs with the study by Kredo, Cooper, Abrams, et al, conducted in four provinces in South Africa, which suggested an urgent need for the National Department of Health (NDoH) to prioritize the existing challenges in the healthcare system in accessing and using medical supplies, which impacted adherence to guidelines [27]. Steinhobel, Mossyn, and Peer outlined that the implementation of the IC program includes maintenance of the infrastructure and the availability of resources [28].…”
Section: Discussionsupporting
confidence: 87%
“…Technical assistance in health systems with varying levels of competence and diverse, localised challenges needs to be flexible and adaptable to effectively respond to the specific contexts in which health services operate. As Kredo et al 7 noted with regard to the implementation of the Clinical Practice Guidelines (CPG) in the South African context, '… for effective CPG implementation in health services to occur, considerations of the unique settings in each province, including culture, geography and social needs, must be undertaken'.…”
Section: Discussionmentioning
confidence: 99%
“…6 Its process is more dynamic and adaptable and is jointly developed and implemented by TA implementers and recipients. 6 Kredo et al 7 noted that in addressing gaps in translating evidence into practice in healthcare settings, tailored, multifaceted approaches that address specific issues seem to be most effective in facilitating change. The healthcare system in SA varies widely in terms of staff capacity, availability of resources and local social, cultural and geographical contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the RSA government allocating 8.5% of gross domestic product (GDP) to healthcare, the health outcomes remain relatively poor compared to other middle-income countries with similar GDP percentage expenditure on health. [35,39] When considering clinical outcomes in diabetic patients, we should include our ability to deal with DFCs across the continuum of care and preventing amputations. The ndings of this study suggest we may still be a long way off from achieving improved health outcomes for diabetic patients.…”
Section: Diagnosis Preceding Amputationmentioning
confidence: 99%